Tennis development at international level: Evolving pathways and holistic approach to nurturing talent - Cahill, G. (Coaching and Sport Science Review, 2024)
This article explores the multifaceted process of talent development in tennis, emphasising the need for a personalised, holistic approach. Traditional linear pathways are giving way to more diverse routes, accommodating each athlete's unique needs and circumstances. The article delves into the ecological model of talent development, considering micro, meso, and macro-level influences on player growth. Globalisation has further expanded opportunities for young talents and coaches, facilitating international competition and advanced educational resources. The role of parents as primary decision-makers is highlighted, underscoring the importance of collaborative efforts between coaches and parents to ensure optimal development. By embracing the complexity and diversity of modern tennis pathways, coaches can better support athletes in achieving their full potential. This comprehensive understanding of the evolving landscape of tennis talent development offers valuable insights for coaches and stakeholders invested in the sport's future.